The Analysis of Education and Training Implementation Effects on Nurse Competence Improvement and Rewards over Nurse Performance at Bunda Margonda Hospital, Depok - Silvia Ayu Rianti; Kemala Rita Wahidi; Agusdini Banun (Penerbit Kemala Indonesia, 2021)
Hospitals must be able to maintain their competitive advantage for long-term success. It takes the performance of nurses to improve a good nursing care services in achieve organizational goals and success. The several factors are affected on nurse performance during providing nursing care namely training, nurse competence improvement, and reward. Thus, this study aimed to analyse the effect of education and training and competence improvement over nurse performance and reward as an intervening variable at Bunda Margonda Hospital, Depok. The research design is use cross sectional technique to obtain the observation data. Here, in this study the population consisted of all nurses at Bunda Margonda Hospital, Depok round 94 respondents. The sampling data was used to obtain saturated sample that took all the study population as a sample. The approach method is applied as a survey method to providing a questionnaire. The measurement method was carried out using a Likert scale while the collected data was processed in descriptive and quantitative analysis. Data analysis testing was performed using Path Analysis AMOS program. Furthermore, the results found that a implementation of education and training had a positive and significant effect on nurse performance (p = 0.047), competence had a positive and significant effect on nurse performance (p = 0.050), reward had a positive and significant effect on nurse performance (p = *** ), education and training had a significant positive effect on rewards received by nurses (p = ***), and competence had a significant positive effect on rewards received by nurses (p = 0.036). The findings of this study indicated that education and training, competence improvement, both had an effect on the nurse’s performance at Bunda Margonda Hospital, Depok with reward as the intervening variable.